2021
DOI: 10.3390/land10080864
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Challenges to the Sustainable Operation of Suburban Villages in a Metropolis: A Comparative Case Study from the Lens of Three Stakeholder-Led Approaches

Abstract: In the rapid urbanization and land development process, the integration of urban and rural areas has accelerated. Alongside this trend, the sustainable operation of suburban villages in metropolitan areas face many difficulties and challenges, especially in terms of the efficient use of land and the coordination of stakeholders’ interests. However, there remains a lack of systematic case studies in the literature targeted toward suburban villages in metropolises. This study selects three typical suburban villa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Our findings reveal that madrasah heads, regardless of their age, will improve their madrasahs' performance-both financial and non-financial performance-if they have political connections. These findings are consistent with the results of previous studies conducted on different types of organizations (Lu et al 2021;Saeed and Ziaulhaq 2019;Kunze et al 2015; Campos-García and Zúñiga-Vicente 2020), and they show that age has a strong relationship with political connections. In addition to that, they also have practical implications regarding performance in terms of listening to and considering the perspectives of other stakeholders when seeking solutions.…”
Section: Political Relations and Characteristics Of Heads Of Madrasahsupporting
confidence: 93%
“…Our findings reveal that madrasah heads, regardless of their age, will improve their madrasahs' performance-both financial and non-financial performance-if they have political connections. These findings are consistent with the results of previous studies conducted on different types of organizations (Lu et al 2021;Saeed and Ziaulhaq 2019;Kunze et al 2015; Campos-García and Zúñiga-Vicente 2020), and they show that age has a strong relationship with political connections. In addition to that, they also have practical implications regarding performance in terms of listening to and considering the perspectives of other stakeholders when seeking solutions.…”
Section: Political Relations and Characteristics Of Heads Of Madrasahsupporting
confidence: 93%
“…Most of the village industries serve the city and combine the natural landscape and cultural resources. Wei introduces the creative processing, planting, and tourism industries for the provision of diversified economic and ecological benefits for suburban villages at the cultural level [22]. Currently, suburban village spaces still have many problems, such as the loss of the village style, the failure of some spaces to meet the needs of the villagers, and the existence of spatial behavioral conflicts between tourists and villagers [23].…”
Section: Introductionmentioning
confidence: 99%
“…Authors suggested that effective policies to mitigate flood risk must be communicated to residents. 0 3 Lu et al [19] The efficient use of land and the coordination of stakeholders' interests in suburban villages are metropolitan challenges. Authors provide practical guidance on how to integrate urban and rural areas.…”
mentioning
confidence: 99%